Performance of wheat (Triticum aestivum) under different irrigation schedules and sowing methods - IDNANI, L K; KUMAR, ASHOK (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during rabi season of 2007–08 and 2008–09 at IARI, New Delhi, to assess theeffects of irrigation schedules and methods of sowing on productivity, water use, economics, soil physical properties andnutrient uptake of wheat (Triticum aestivum L. emend. Fiori & Paol) on sandy loam soil. Five irrigation schedules (I1,Irrigation at CRI, I2, CRI + 200 mm CPE; I3, CRI + 150 mm CPE; I4, CRI + 100 mm CPE; and I5, CRI + 50 mm CPE) were allotted in horizontal strips and three sowing methods (M1, Conventional, M2, FIRBS and M3, side sowing on ridges) were allotted in vertical strips in strip plot design replicated thrice. The FIRBS planting and irrigation at CRI stage + 100 mm CPE registered significantly highest grain yield, straw yield, harvest index, net return, benefit: cost ratio, cumulative infiltration, N, P and K uptake.